Judo Information Site - Ohlenkamp, N. (2001)
The purpose of the Judo Information Site is to promote Judo around the world by educating the general public, Judo students, and Judo instructors about the various aspects of Judo. Judo can be more than an Olympic sport or a martial art, it is a way of life for many people who practice it. This site allows the learning to continue off the mat, providing for a more complete understanding of the richness of Judo.